Transanal Total Mesorectal Excision: Description of the Technique - Trépanier, Jean-Sébastien (Clin Colon Rectal Surg, 2020)
Surgery remains the gold standard for the treatment of locally advanced rectal cancer. The most effective approach to reduce locoregional recurrence is total mesorectal excision (TME). However, obtaining an optimal TME is demanding, especially in low rectal tumors and anatomically unfavorable pelvis. Transanal TME (taTME) was developed to facilitate low pelvis dissection and potentially provide optimal outcomes for oncologic resection. Current studies have reported satisfactory short-term outcomes. However, taTME is a technically challenging procedure and must be learned in an appropriate training process to allow for a safe implementation. Previous experience in laparoscopic and transanal surgery is strongly recommended. In this work, we provide a detailed discussion of the technique, based on the realization of more than 400 taTME interventions.